Empowering the Community Through Training in the Production of Flavored Banana Chips as a Strategy for Product Diversification in Bonde Village, Pamboang District, Majene Regency: Pemberdayaan Masyarakat Melalui Pelatihan Pembuatan Keripik Pisang Aneka Rasa Sebagai Upaya Diversifikasi Produk Olahan Pisang di Desa Bonde Kecamatan Pamboang Kabupaten Majene - Tiffany, Margaretha Hanna; Fathanah, Nurul; Samang, Andi Marlisa Bossa; Syah, Ikrar Taruna (Jurnal Inovasi dan Pengabdian Kaa Mieera, 2025)
This community service activity was carried out in Bonde Village, Pamboang District, Majene Regency, to empower the local community through training in the production of flavored banana chips as a strategy for product diversification based on local potential. Bonde Village has several leading agricultural commodities, one of which is bananas. However, the utilization of bananas is still limited to fresh consumption or direct sale at relatively low economic value. The activity consisted of three stages: preparation, training, and evaluation. During the training phase, participants received material on the objectives of product diversification, followed by hands-on practice in making banana chips with chocolate and balado flavor variants. Evaluation was conducted using pre-test and post-test methods to assess the improvement in participants’ understanding. The results showed a significant increase in participants' understanding of the diversification process and banana chip production (85% and 95%, respectively), as well as an increased interest in developing the product as a business opportunity (75%). This activity is expected to serve as an initial step in developing local potential and enhancing the economic self-reliance of the village community.